2019
DOI: 10.1177/0020872819858744
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a culture of workplace safety in human service organizations: A qualitative analysis

Abstract: Workplace cultures are an important component in creating safe work environments. In-depth qualitative interviews ( n = 85) were conducted with human service workers of a large publicly administered human service organization in Canada to learn more about the organizational and/or workplace conditions that contribute to a safety culture. Findings reveal that a safety culture within this human service workplace is defined by values or attitudes associated with safety and structured mechanisms that help promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Similar to previous international research (e.g. Littlechild 2003;Shier et al 2019;Vogus et al 2016), our findings suggest that social workers experience inadequate support from employers, a culture of silence, and normalization when dealing with client violence. This tendency is explained partly by workloads that supersede attention to the risk of violence (Turpin et al 2020) and legislation that makes employers and employees jointly responsible for safety promotion, with assaulted/threatened employees experiencing self-blame as a result (Wikman 2012).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to previous international research (e.g. Littlechild 2003;Shier et al 2019;Vogus et al 2016), our findings suggest that social workers experience inadequate support from employers, a culture of silence, and normalization when dealing with client violence. This tendency is explained partly by workloads that supersede attention to the risk of violence (Turpin et al 2020) and legislation that makes employers and employees jointly responsible for safety promotion, with assaulted/threatened employees experiencing self-blame as a result (Wikman 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Social workers struggle to accept this notion, well aware of the looming and undesirable effects of violence. The culture of normalization and silence makes social workers vulnerable for repeated assaults and threats, while experiencing inadequate support from their supervisors/managers (Littlechild et al 2016;Shier et al 2019;Vogus et al 2016). In this way, structures and practices in social service agencies may unintentionally contribute to a toxic environment that heightens social workers' stress.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, respondents answered between "always" and "very always" for all items in the management aspect with slightly different mean scores (4.57 to 4.68). This emphasizes that the effective communication is important to avoid mishaps in the laboratory [16].…”
Section: Resultsmentioning
confidence: 99%
“…The team succeeded in improving its employee engagement index by an average of 11% over the last 3 years, as demonstrated by the annual employee's satisfaction survey. Studying human service employees in Canada, Shier, Turpin, Nicholas, and Graham (2019) concluded that a safe workplace is one that creates belonging, encourages openness, promotes cooperation, and inspires a desire to excel.…”
Section: The Finding: Creating An Environment Of Trust and Safetymentioning
confidence: 99%